2007
DOI: 10.1021/bp060382y
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Synthesis of Aspartame Precursor Using Organic-Solvent-Stable PST-01 Protease in Monophasic Aqueous-Organic Solvent Systems

Abstract: The PST-01 protease is a metalloprotease that has zinc ion at the active center and is very stable in the presence of water-soluble organic solvents. The reaction rates and the equilibrium yields of the aspartame precursor N-carbobenzoxy-L-aspartyl-L-phenylalanine methyl ester (Cbz-Asp-Phe-OMe) synthesis from N-carbobenzoxy-L-aspartic acid (Cbz-Asp) and L-phenylalanine methyl ester (Phe-OMe) in the presence of water-soluble organic solvents were investigated under various conditions. Higher reaction rate and y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The protease PST-01, from Pseudomonas aeruginosa, was one of the first reported solvent-tolerant proteases and can be overproduced from the native host to ∼80 mg/liter of culture (103). The wild-type protease is stable to many polar organic solvents, but its peptide synthesis rate is low (104). However, the activity (k cat ) was improved tenfold by a single amino acid mutation of Y114S, made by comparison with a homologous thermophilic metalloprotease, Thermolysin (105).…”
Section: Proteasesmentioning
confidence: 99%
“…The protease PST-01, from Pseudomonas aeruginosa, was one of the first reported solvent-tolerant proteases and can be overproduced from the native host to ∼80 mg/liter of culture (103). The wild-type protease is stable to many polar organic solvents, but its peptide synthesis rate is low (104). However, the activity (k cat ) was improved tenfold by a single amino acid mutation of Y114S, made by comparison with a homologous thermophilic metalloprotease, Thermolysin (105).…”
Section: Proteasesmentioning
confidence: 99%
“…The highest yield 82.2% in aqueous medium was obtained from 100 mM Z-l-Asp and 500 mM l-PheOMe at pH 6.0. The efficient synthesis of Z-APM from 30 mM Z-l-Asp and 500 mM l-PheOMe in 50% DMSO at pH 7.0 with the highest yield of 83.0% was reported by Ogino group using protease PST-01, which has the same amino acid sequence with protease PT121 [12]. The distinct effect of DMSO on Z-APM synthesis was probably Table 1 shows that the molar solubility of Z-APM was 8.2 × 10 −2 M at pH 7.0.…”
Section: Effect Of Dmso On the Synthesis Of Z-apm At Ph 60mentioning
confidence: 96%
“…However, production of Z-APM is difficult to scale up due to the complicated purification of the product, as well as the cost of the reaction medium [11]. Z-APM was also synthesized by Pseudomonas aeruginosa protease PST-01, with an 83.0% yield, in the presence of 50% (v/v) dimethyl sulfoxide (DMSO) at pH 7.0 using 30 mM Z-l-Asp and 500 mM l-PheOMe [12].…”
Section: Introductionmentioning
confidence: 99%
“…The use of organic solvents, usually required for performing enzymatic peptide synthesis [301], imposes additional restrictions on process design and engineering, and contradicts the clean technology concept [245,302], so major efforts are being directed toward their replacement by greener systems, among which ionic liquids [82,198] and solid or semisolid reaction media are prominent [196,[303][304][305]. Recently, Meng et al [291] reported the enzymatic synthesis of the CCK pentapeptide (CCK-5) where the coupling was conducted in aqueous buffer and no hazardous chemicals were necessary.…”
Section: Enzymatic Synthesis Of Peptidesmentioning
confidence: 99%